Copépodos parásitos (Siphonostomatoida: Pandaridae) de Prionace glauca e Isurus oxyrinchus, capturados en la costa central de Chile (Revista de Biología Marina y Oceanografía, 2018)
In the Chilean coast, sharks and rays are one of the least studied fish groups, therefore quantitative data about theirparasites are scarce or almost non existing. Copepod parasites were collected from different sites along corporal body of Prionace glauca (n= 12) and of Isurus oxyrinchus (n= 1) captured onboard cruise OCEARCH during March and April 2014. Three species belonging to the Pandaridae family were identified: Echthrogaleus coleoptratus, Dinemoura producta and Nessipus orientalis. The latter species is here recorded for the first time in Chilean waters. These copepods did not show infection site preferences along host body. Considering the wide range of hosts described for these parasite species, it is concluded they are generalist parasites of wide geographic distribution.